Principal’s interpersonal communication In improving Islamic Junior High School teachers’ motivation - Ali Iskandar (Nalar: Journal of Pedagogy and Society, 2021)
The rationale of this research was the issue of teachers’ motivation level in carrying out their jobs. Motivation might be affected by many factors including principal’s interpersonal communication. This qualitative field research aimed to investigate principal’s interpersonal communication, teachers’ job motivation, and factors that affected Principal’s Interpersonal Communication at Islamic Junior High School Siak Hulu, Kampar. The data were collected from six informants by applying observations, interviews, and documentation. Furthermore, the collected data were analyzed through four steps including data collection, data reduction, data presentation, and conclusion/results verification. Results showed that principal’s interpersonal communication was implemented through openness, empathy, support, and equality. In addition, teachers’ job motivation at Islamic Junior High School Siak Hulu, Kampar was indicated by their perseverance, passion, discipline, and fondness to challenge. Furthermore, principal’s interpersonal communication was affected by ability, capability, leadership model, work environment.